AN ANALYSIS OF STUDENTS' LINGUISTIC DIFFICULTIES IN WRITING RECOUNT TEXT AT THE TENTH GRADE TEKNIK PENGEBORAN MINYAK DAN GAS (TPMG) SMK NEGERI 1 MANDAU - Deny Silvia; Mohd. Rafi Riyawi; Lilis Sopia (STIT Al Mubarok Bandar Mataram - Lampung Tengah, 2022)
The purpose of this study is to analyze what are the students' difficulties in writing English using recount text. This research is a quantitative approach descriptive research design involving 33 Tenth grade students of TPMG. The data collection technique is a test. There are several steps to analyze the data: analyzing the students' work, calculating the average score using descriptive statistics and the last step is descriptive analysis. The results showed that the students' difficulties in writing English in the tenth grade of TPMG were Vocabullary 33%, Grammar 40% and language use 27%. So the highest difficulty experienced by these students lies in grammar with a percentage of 40%